Land suitability analysis based on soil properties and GIS for improving rice productivity in Bihar, India - Manibhushan, -; Singh, Anil Kumar; Mondal, S; Chandra, N (Bangladesh Journal of Botany, 2019)
This study was conducted for land classification and analysis of image for defining the land suitability for improving rice crop productivity. Several criteria were considered for the determination of land suitability for rice crop. IRS P6 LISS III image and digitized toposheet of Madhubani district were used for the study. Taking all the variables into accounts, a comprehensive block-wise land suitability map for rice crop of the district has been developed using multicriteria approach and GIS. It was found that 22% of the total rice growing area i.e. 72418 ha are highly suitable, 63% (224512 ha) are moderately suitable, 15% (50372 ha) are marginally suitable and around 1% (3356 ha) is unsuitable for rice crop in Madhubani district. However, it is presumed that the suitability of the rice growing areas may increase or decrease depending on the changes in soil parameters, rainfall, water availability, and other associated factors .